Abstracts of the 14th Congress of the African Association of Nephrology (Yaoundé, 14-18 March 2017) - Ashuntantang, Gloria (African Journal of Nephrology, 2017)
Abstracts of the joint AFRAN, AFPNA and SOCANEPH Congress held in Yaoundé, Cameroon, 14-18 March 2017. Abstracts published as received.